Micromechanical homogenisation of steel bars in reinforced concrete for damage analysis. (June 2022) - Drougkas, Anastasios; Sarhosis, Vasilis; Thermou, Georgia
Abstract: A homogenisation scheme based on inclusion modelling is coupled with constitutive laws for damage and implemented in a finite element model for the simulation of concrete and reinforcement bar damage in reinforced concrete structures. The scheme is employed for simulating the behaviour of evenly distributed reinforcement and adapted for the simulation of zones with concentrated reinforcement in structural members. The model is validated against experimental tests from the literature carried out on reinforced concrete members subjected to bending and direct tension. The model captures the main characteristics of the behaviour of and damage in the constituent materials of reinforced concrete without resorting to individual meshing of the embedded bars and with very low computational cost. Highlights: A homogenisation scheme is applied in RC for simulating reinforced zones and surfaces. Both distributed and concentrated reinforcement is simulated in full scale members. Stresses, strains and damage in rebars and concrete can be calculated in a continuum FE mesh.